Hierarchical self-organization of soft patchy nanoparticles into morphologically diverse aggregates. (July 2017) - C. Gârlea, Ioana; Bianchi, Emanuela; Capone, Barbara; Rovigatti, Lorenzo; N. Likos, Christos
Abstract: We present a concise review of the large variety of self-assembly scenarios observed in solutions of diblock copolymer stars with a solvophilic inner block and a solvophobic outer block. A variety of modeling approaches and simulation techniques at different levels of detail reveals that individual molecules assume configurations akin to patchy colloids, but with a patchiness that depends on physical parameters and can adjust to external stimuli such as temperature and pH. These soft, patchy building blocks inter-associate at finite concentrations into micellar or gel-like solutions, including spherical and wormlike micelles, or they display macroscopic phase separation. The connections between single-molecule conformation and the structure of the concentrated solution are discussed, and coarse-grained strategies for these novel molecular entities are critically compared to one another. Graphical Abstract: